# `f(x) = x e^x csc(x)` Differentiate.

*print*Print*list*Cite

### 1 Answer

To find

`y'=d/(dx) x*e^x csc(x)`

let `a= x*e^x`

so,

`y'=d/(dx) (a*csc(x))`

`= (d/(dx) a) *csc(x) + a* d/(dx)(csc(x))`

substituting` a = x*e^x`

so` a' = (d/(dx) a)`

`= (d/(dx) x*e^x) = x*e^x + e^x`

and

`d/(dx)(csc(x)) = -csc(x)cot(x)`

so ,

`y'=(d/(dx) a) *csc(x) + a* d/(dx)(csc(x))`

`= (x*e^x + e^x)*csc(x) + (x*e^x)* (-csc(x)cot(x))`

`= (e^x)(1+x)*csc(x)- (x*e^x)* (csc(x))*(cot(x))`

`= (e^x)*csc(x)[(1+x)-x*(cot(x))]`